Pengembangan Media Game Interaktif Wordwall Untuk Memfasilitasi Kemampuan Berpikir Komputasional Anak Usia 5-6 Tahun - Syifa Faujiyah; Taopik Rahman; Anggi Maulana Rizqi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Computational thinking is a crucial 21st-century skill that needs to be cultivated from an early age to prepare children for the challenges of the digital era. However, current instructional practices in early childhood education (PAUD) settings still rely heavily on worksheets as the primary medium; consequently, learning activities tend to be monotonous and do not optimally support the development of children's computational thinking skills. Addressing this issue, this study aims to develop Wordwall-based learning media to facilitate computational thinking skills in children aged 5–6 years. The study employs an Educational Design Research approach, adapting the McKenney and Reeves model, which comprises three main stages: analysis and exploration, design and development, and evaluation and reflection. The resulting product consists of four interactive Wordwall-based games specifically designed to stimulate elements of computational thinking, including decomposition, pattern recognition, abstraction, and algorithms. Data collection was conducted through observation, interviews, validation by subject matter and media experts as well as practitioners, and documentation. Subsequently, the data were analyzed using descriptive qualitative and quantitative approaches to assess the feasibility of the developed media. The results indicate that the Wordwall media was deemed feasible based on assessments by subject matter and media experts, following a series of revisions based on validator feedback. The media proved capable of creating a learning experience that is more interactive, engaging, and aligned with the learning characteristics of young children. Therefore, the Wordwall media is considered suitable for use as an alternative learning tool to facilitate computational thinking skills in children aged 5–6 years within early childhood education settings